Gastrointestinal surgery in the COVID-19 pandemic - Marek Durlik (Gastroenterology Review)
The data presented from a tertiary General University Hospital in Greece are interesting [1]. The comparable number of patients during the COVID-19 pandemic and the non-Covid era is a unique observation. A point to consider is that the study comes from a single centre, based on a relatively small number of cases.